The use of ontology using Protégé ontology editor tool in developing syllabus management system - Mohd Jayothisa, Chandrika; Abdullah, Mohd Syazwan (2010)
The management and the academic staffs of the Centre for Diploma Programme’s (CDP) will usually gather and prepare hard copies of syllabi as part of documentation collection in order to obtain the MQA’s accreditation for the courses offered.The creation of Syllabus Management System for the DIT has helped the management staff in organizing, updating and retrieving Diploma in Information Technology’s (DIT) syllabi.The concept of ontology has successfully used throughout the development of the system.Unified Modeling Language (UML) is used to capture the requirement models while ontology development methodology is used during the development stage.The prototype of the system is deployed on the Protégé ontology editor tool.